Redox imbalance in Crohn's disease patients is modulated by Azathioprine. (1st January 2021) - Tavassolifar, Mohammad Javad; Changaei, Mostafa; Salehi, Zahra; Ghasemi, Fatemeh; Javidan, Moslem; Nicknam, Mohammad Hossein; Pourmand, Mohammad Reza
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory disease without a specific cause. Inflammation in these patients can disturb the oxidants/antioxidants balance and results in oxidative stress that plays a destructive role. This study aimed to evaluate the gene expression of sod1, sod2, cat, nrf2 and gp91phox in CD patients before and after Azathioprine (Aza) consumption. Method: Peripheral bloodmononuclear cells (PBMCs) were separated from CD patients ( n = 15, mean age = 33.6 ± 1.8) before and after treatment with Aza and healthy controls ( n = 15, mean age = 31.5 ± 1.2). The expression levels of sod1, sod2, cat, nrf2 and gp91phox were measured in byusing real-time qRT-PCR technique. Result: The expression levels of gp91phox ( P- value < 0.001), cat ( P- value < 0.05), sod1 ( P -value < 0.001), nrf2 ( P -value < 0.001) were significantly increased compared to control group. Following treatment with Aza, the decreased expression levels of gp91phox ( P- value < 0.05), cat ( P- value < 0.05), sod1 ( P -value < 0.001) and nrf2 ( P -value < 0.001) were observed in CD patients. Conclusion: Overall, our results showed that prescription of Azathioprine can lead to the altered expression of redox system-related genes in patients with CD.